Studi Literatur Pengaruh Teknik Pengangkatan Pada Semua Pola Pangkas Rambut - Ifa Nurhayati; Anik Maghfiroh; Wahyu Widaningsih; Lucky Amelia P (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to investigate the impact of lifting techniques in various haircut styles and how this affects the final outcome and appearance of the hair. This literature review analyzes various lifting methods, including vertical, horizontal, and diagonal elevation, as well as the implementation of each technique on different haircut styles such as bob, layers, pixie, and shag. The results of the research show that choosing the right lifting technique can significantly influence the texture, volume, and shape of the hair, as well as create a more accurate cut in line with desired hair fashion trends. Additionally, this study reveals the function of lifting techniques in creating a balance between control and freedom of hair movement, as well as their impact on long-term hair health. . This research offers an understanding for experts in the beauty sector to identify and apply lifting techniques that suit the client's needs, in order to achieve the best haircut that is in line with current trends.